Chromosome number of some species of Hymenophyllaceae from Thailand - SIWAKORN CHOKRASSAMEEHIRUN; EKAPHAN KRAICHAK; TASSANAI JARUWATTANAPHAN (Society for Indonesian Biodiversity, 2024)
Abstract. Chokrassameehirun S, Kraichak E, Jaruwattanaphan T. 2024. Chromosome number of some species of Hymenophyllaceae from Thailand. Biodiversitas 25: 4389-4396. Hymenophyllaceae, known by the common name filmy ferns family, a basal family of leptosporangiate ferns, comprises ca.450 species and is distinctive amongst the entire pteridophytes by mostly unistratrose lamina. Classification and evolution of the family have fascinated botanists for many decades. Chromosome numbers in this family provide insights into evolutionary trends and have been useful for genus delimitation in recent classification schemes. However, interest in studying chromosome counts has declined in recent years. This study aimed to provide additional chromosome counts from Thailand species. Mitotic chromosomes were observed by using the hematoxylin squash technique. Five species belonging to Abrodictyum, Crepidomanes, and Hymenophyllum were examined, including H. acanthoides (Bosch) Rosenst. (2n=2x=41) and H. longifolium Alderw. (2n=2x=72), which were recorded for the first time. All specimens are of the diploid cytotype based on the chromosome base number of the genus. The results support aneuploid reduced evolution in Hymenophyllum, especially in subg. Hymenophyllum, with H. acanthoides showing a unique number, is assumed to have been reduced from 2n=42, which is the most typical within the subgenus. Additionally, A. obscurum (Blume) Ebihara & K.Iwats. var. obscurum (2n=2x=66) and H. exsertum Wall. ex Hook. (2n=2x=42) show consistent numbers within the species, whereas C. minutum (Blume) K.Iwats. (2n=2x=72) displayed some variation within the species, suggesting multiple cytotypes and reticulate evolution. More sampling is still needed for all species to fill the gap in the evolution study for this fern family.